Anticancer potential of nanogold conjugated toxin GNP-NN-32 from Naja naja venom - Attarde,Saurabh S. (2020)
Abstract Background: Cancer is the second most common fatal disease in the world, behind cardiovascular disorders in the first place. It accounts for around 0.3 million deaths per year in India due to the lack of proper diagnostic facilities, prevention and treatment. Current therapeutic methods do not provide adequate protection and affect normal cells along with cancerous ones. Thus, there is a need for some alternative therapeutic strategy, preferably from natural products, which have been traditionally used for treatment of various diseases in the country. Methods: In this study, we have conjugated purified NN-32 toxin from Naja naja venom with gold nanoparticles and its anticancer potential was evaluated against human breast cancer cell lines. UV-Vis spectroscopy, dynamic light scattering, transmission electron microscopy, atomic force microscopy and zeta potential analysis were the techniques used for characterization of GNP-NN-32. Results: GNP-NN-32 showed dose- and time-dependent cytotoxicity against breast cancer cell lines (MCF-7 and MDA-MB-231). NN-32 and GNP-NN-32 induced apoptosis in both breast cancer cell lines. The results of CFSE cell proliferation study revealed that NN-32 and GNP-NN-32 arrested cell division in both MCF-7 and MDA-MB-231 cell lines resulting in inhibition of proliferation of these cancer cells. Conclusion: GNP-NN-32 showed an anticancer potential against human breast cancer cell lines. Analysis of detailed chemical characterization along with its cytotoxic property might help to perceive a new dimension of the anti-cancer potential of GNP-NN-32 that will enhance its biomedical function in near future.